PENGARUH KEDISPLINAN KERJA, KOMUNIKASI INTERPERSONAL DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN di PT KUSUMA SANDANG MEKARJAYA (KSM) - Linggar Saputri (MNJ 15 UMY 570, 2015)
*321 This research aimed at identifying the effect of discipline, interpersonal communication and work environment towards the performance of employees at PT Kusuma Sandang Mekarjaya (KSM) Yogyakarta. The result of this research would be used to inform what factors that motivate the employees’ performance. This research was conducted at PT Kusuma Sandang Mekarjaya (KSM) Yogyakarta, and the respondents were the employees who have been working at the spinning unit for 1 year. The data were collected through a survey using purposive sampling, by distributing questionnaire to 75 respondents. The data were analyzed using statistical product and service solution (SPSS) and tested using Validity Test and Reliability Test. The result of the research shows that discipline significantly affect the employees’ performance, while interpersonal communication has negative effect and is not significant. Similarly, physical work environmenthas negative effect and is not significant for the the employees’ performance.